Effect of Health Literacy on Quality of Life amongst Patients with Ischaemic Heart Disease in Australian General Practice. - David Alejandro González-Chica; Zandile Mnisi; Jodie Avery; Katherine Duszynski; Jenny Doust; Philip Tideman; Andrew Murphy; Jacquii Burgess; Justin Beilby; Nigel Stocks (PLoS ONE)
Background Appropriate understanding of health information by patients with cardiovascular disease (CVD) is fundamental for better management of risk factors and improved morbidity, which can also benefit their quality of life. Objectives To assess the relationship between health literacy and health-related quality of life (HRQoL) in patients with ischaemic heart disease (IHD), and to investigate the role of sociodemographic and clinical variables as possible confounders. Methods Cross-sectional study of patients with IHD recruited from a stratified sample of general practices in two Australian states (Queensland and South Australia) between 2007 and 2009. Health literacy was measured using a validated questionnaire and classified as inadequate, marginal, or adequate. Physical and mental components of HRQoL were assessed using the Medical Outcomes Study Short Form (SF12) questionnaire. Analyses were adjusted for confounders (sociodemographic variables, clinical history of IHD, number of CVD comorbidities, and CVD risk factors) using multiple linear regression. Results A total sample of 587 patients with IHD (mean age 72.0±8.4 years) was evaluated: 76.8% males, 84.2% retired or pensioner, and 51.4% with up to secondary educational level. Health literacy showed a mean of 39.6±6.7 points, with 14.3% (95%CI 11.8-17.3) classified as inadequate. Scores of the physical component of HRQoL were 39.6 (95%CI 37.1-42.1), 42.1 (95%CI 40.8-43.3) and 44.8 (95%CI 43.3-46.2) for inadequate, marginal, and adequate health literacy, respectively (p-value for trend = 0.001). This association persisted after adjustment for confounders. Health literacy was not associated with the mental component of HRQoL (p-value = 0.482). Advanced age, lower educational level, disadvantaged socioeconomic position, and a larger number of CVD comorbidities adversely affected both, health literacy and HRQoL. Conclusion Inadequate health literacy is a contributing factor to poor physical functioning in patients with IHD. Increasing health literacy may improve HRQoL and reduce the impact of IHD among patients with this chronic CVD.